Peningkatan Pemahaman Kajian Haid, Nifas, dan Istihadhoh Bagi Wanita di Desa Sukamandi Subang Jawa Barat - Mursyidi, Wathroh; Dwi Kumalasari, Eva (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: This community service activity was motivated by the low understanding of Islamic jurisprudence (fiqh) laws among mothers and young women in Sukamandi Village, Sagalaherang, particularly regarding menstruation, postpartum bleeding, and istihadhoh. Misunderstandings often lead to confusion about purity, worship obligations, and obligatory bathing. The program aimed to increase participants' awareness and understanding of sharia provisions related to women's blood based on authoritative references. Method: The Participatory Action Research (PAR) method was used, including participant registration, socialization, lectures, case-based discussions, and evaluation. A total of 21 participants attended the program. Results: Post-activity evaluation showed an 82% improvement in understanding compared to pre-activity assessments, with 90% of participants actively engaged during discussions and Q&A sessions. Participants were able to answer most of the case studies correctly. Conclusion: The program effectively enhanced women's understanding of fiqh topics related to menstruation, postpartum bleeding, and istihadhoh in Sukamandi Village.